Media studies : text, production and context. - Long, Paul, ....-; Wall, Tim, ....- (Essex : Pearson Educational Limited, 2009)
This groundbreaking and innovative introduction to Media Studies will afford undergraduate and mature students a comprehensive overview of the subject area. It will set students firmly on course to be critical, informed and canny operators within the discipline. The text is pedagogically rich and covers a wide range of topics from the history of media right through to coverage of new media. The text interweaves theory, practice, and professional issues throughout, and will engage the reader fully with the principal issues, challenges and paradigms in the discipline. Through a breadth of reference and support resources, students will activley grapple with a variety of media at both a practical and intellectual level. Students will emerge with a broad range of perspectives, a strong conceptual sense of the area and a firm foundation to take a critical approach to their studies at higher levels. Media Studies: texts, production and context will be essential reading for undergraduate and postgraduate students of media studies, cultural studies, communication studies, film studies, the sociology of the media, popular culture and other related subjects.
Keywords: Media